Condensin-mediated chromosome organization and gene regulation - Lau, Alyssa C.; Csankovszki, Györgyi (Frontiers in Genetics, 2015)
In many organisms sexual fate is determined by a chromosome-based method which entails a difference in sex chromosome-linked gene dosage. Consequently, a gene regulatory mechanism called dosage compensation equalizes X-linked gene expression between the sexes. Dosage compensation initiates as cells transition from pluripotency to differentiation. In C. elegans, dosage compensation is achieved by the dosage compensation complex (DCC) binding to both X chromosomes in hermaphrodites to downregulate gene expression by two fold. The DCC contains a subcomplex (condensin IDC) similar to the evolutionarily conserved condensin complexes which play a fundamental role in chromosome dynamics during mitosis. Therefore, mechanisms related to mitotic chromosome condensation are hypothesized to mediate dosage compensation. Consistent with this hypothesis, monomethylation of histone H4 lysine 20 (H4K20) is increased, whereas acetylation of histone H4 lysine 16 (H4K16) is decreased, both on mitotic chromosomes and on interphase dosage compensated X chromosomes in worms. These observations suggest that interphase dosage compensated X chromosomes maintain some characteristics associated with condensed mitotic chromosome. This chromosome state is stably propagated from one cell generation to the next. In this review we will speculate on how the biochemical activities of condensin can achieve both mitotic chromosome compaction and gene repression.